Service evaluation of a Human Givens Therapy service for veterans. (23rd May 2019) - Burdett, H; Greenberg, N
Abstract: Background: PTSD Resolution is a charitable provider of mental health support and treatment via Human Givens Therapy to members of the Armed Forces Community. This study utilized data from their client database to evaluate outcomes of their services. Aims: To determine whether treatment by the service resulted in improvements in mental health; to the extent possible, compare these outcomes with those of NHS IAPT (National Health Service – Improving Access to Psychological Therapies) services; and to evaluate how other factors, notable reported stress levels and prior treatment, impacted outcomes. Methods: Administratively collected data from the service provider collected between 2014 and 2016 were utilized. Clients still undergoing services were excluded. The CORE-10 (10-item Clinical Outcomes in Routine Evaluation) measure was used as the outcome measure. Demographic factors examined included age, sex, employment, accommodation, relationship status, distress at the time of presentation and prior treatment history. The effect of the factors was analysed using χ 2 test as well as linear regression and Poisson regression analyses according to the nature of the variable. Results: PTSD Resolution clients appeared to show a similar degree of improvement as IAPT patients. Job-seekers and those who are living alone benefited less from the treatment. Despite high levels of distress and prior treatment among this client group, these factors did not seem to affect treatment outcomes. Conclusions: The services of this provider appear to be an acceptable alternative for IAPT treatment, to the degree such a comparison can be made given differences in measures and client groups.